The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/0975-7406.137469
|View full text |Cite
|
Sign up to set email alerts
|

Nonsyndromic oligodontia in siblings: A rare case report

Abstract: A syndrome is a medical condition that is characterized by a particular group of signs and symptoms, involving several organ systems. Oligodontia is defined as the developmental absence of six teeth or more, excluding third molars. Oligodontia can be classified as syndromic or nonsyndromic. Nonsyndrome oligodontia is a developmental dental anomaly without involvement of other organs. The consequences of missing teeth include abnormal occlusion or altered facial appearance, which can cause psychological distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…This granular structure is similar to that reported earlier for cassava starch. [ 48,49 ] No significant changes in the granule morphology either with respect to plant growth or cultivar differences could be observed. However, granular size showed statistically significant differences with the age of the crop ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This granular structure is similar to that reported earlier for cassava starch. [ 48,49 ] No significant changes in the granule morphology either with respect to plant growth or cultivar differences could be observed. However, granular size showed statistically significant differences with the age of the crop ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The heritability of congenitally missing teeth has been shown in many studies. The genetic factors may be dominant or recessive and it is obvious that in many cases multiple genetic and environmental factors are acting together [8].…”
Section: Discussionmentioning
confidence: 99%
“…Rasmussen reported nine cases of non syndromic oligodontia with 14-24 missing teeth excluding third molar [13]. Nagveni, et al, have reported a case of non syndromic oligodontia in a 13-year-old patient with 14 missing teeth [14] non syndromic oligodontia in a 9-year-old patient with 26 missing teeth [8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is evident that numerous cases involve the combined influence of multiple genetic and environmental factors. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%